The Development of Green BIM Based Standard Operating Procedure on Schematic Design Phase of Building Projects to Improve Duration Performance From The Perspective of Architecture Consultant - Rianita Suryani; Leni Sagita Riantini (Journal of International Conference Proceedings (JICP), 2019)
Building Information Modeling (BIM) is one of the technologies that can help the building design process with green building concept and BIM can evaluate energy performance and ongoing assessments that are interpreted by Green BIM. This research aims to determine the activities, stakeholders and the role of Green BIM to improve duration performance on schematic design phase of building projects, which was developed with a Green BIM based Standard Operating Procedure. The methodology is based on secondary data and interview with the respondents who contribute in Architecture Consultant Office. The result is Standard Operating Procedure and illustrates the relationship between activities in each strategy on schematic design phase, the roles of stakeholders and the data exchange flow.